The prognostic impact of PD-L1 and CD8 expression in anal cancer patients treated with chemoradiotherapy - Chan, Angela MY.; Roldan Urgoiti, Gloria; Jiang, Will; Lee, Sandra; Kornaga, Elizabeth; Mathen, Peter; Yeung, Rosanna; Enwere, Emeka K.; Box, Alan; Konno, Mie; Koebel, Martin; Joseph, Kurian; et al. (Frontiers in Oncology, 2022)
Background Programmed death-ligand 1 (PD-L1) expression has been shown to be prognostic in many cancer types and used in consideration of checkpoint inhibitor immunotherapy. However, there are very limited and conflicting data on the prognostic impact of PD-L1 in patients with anal squamous cell carcinoma (ASCC). The objectives of this study were to measure the expression of PD-L1 and CD8 in patients with ASCC treated with radical chemoradiotherapy (CRT) and to correlate tumor expression with progression-free survival (PFS) and overall survival (OS). Methods Ninety-nine patients with ASCC treated with primary CRT at two tertiary care cancer centers between 2000 and 2013, with available pre-treatment tumors, were included. Tissue microarrays (TMAs) from pre-treatment tumor specimens were stained for PD-L1 and CD8. PD-L1 expression in the tumor and stroma was quantified using HALO image analysis software, and results were interpreted using quantitative methods. The density of CD8 cells within the tumor was interpreted by a trained pathologist semi-quantitatively, using a 0-4 scoring system. Kaplan-Meier analysis with log-rank was used to determine the significance in the association of tumor markers with PFS and OS. Cox multivariate analysis was used to explore independent predictors of PFS and OS. Results Of the 99 patients, 63 (64%) had sufficient tumor samples available for full analysis. CD8 high status was documented in 32 of 63 (50.8%) % of cases. PD-L1 expression was positive in 88.9% of cases. Approximately half the patients had tumor PD-L1 ≥ 5%. Patients with tumor PD-L1 ≥ 5% had better OS vs those with lower expression, HR=0.32 (95% CI 0.11-0.87), p=0.027; 10 years OS: 84% for tumor PD-L1 ≥ 5% vs 49% for PD-L1 < 5%. PD-L1 expression was not associated with PFS. On multivariate analysis, tumor PD-L1 ≥ 5% showed a trend to statistical significance for better OS, HR=0.55 (95% CI 0.12- 1.00), p=0.052. Conclusions Tumor PD-L1≥5% is associated with OS in patients with ASCC treated with CRT. PD-L1 expression status using this unique cut-point warrants further validation for prognostication in patients with this disease. Future studies are required to determine the benefit of alternative treatment strategies based on PD-L1 status.